Regulation and therapy: the role of ferroptosis in DLBCL - Wang, Yifan; He, Zhengmei; Dong, Xinyu; Yao, Yiming; Chen, Qiuni; Shi, Yuye; Deng, Yuan; Zhang, Quane; Yu, Liang; Wang, Chunling (Frontiers in Pharmacology, 2025)
Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of B-cell non-Hodgkin’s lymphoma (NHL), up to 30%–40% of patients will relapse and 10%–15% of patients have primary refractory disease, so exploring new treatment options is necessary. Ferroptosis is a non-apoptotic cell death mode discovered in recent years. Its occurrence pathway plays an essential impact on the therapeutic effect of tumors. Numerous studies have shown that modulating critical factors in the ferroptosis pathway can influence the growth of tumor cells in hematological malignancies including DLBCL. This review highlights recent advances in ferroptosis-related genes (FRGs), including STAT3, Nrf2, and ZEB1, and focuses on the clinical potential of ferroptosis inducers such as IKE, α-KG, DMF, and APR-246, which are currently being explored in clinical studies for their therapeutic effects in DLBCL. Correlational studies provide a novel idea for the research and treatment of ferroptosis in DLBCL and other hematological malignancies and lay a solid foundation for future studies.